The Cambridge companion to Jane Austen - Copeland, Edward; McMaster, Juliet (Cambridge companions to literature., 2010)
Jane Austen's stock in the popular marketplace has never been higher, while academic studies continue to uncover new aspects of her engagement with her world. This fully updated edition of the acclaimed Cambridge Companion offers clear, accessible coverage of the intricacies of Austen's works in their historical context, with biographical information and suggestions for further reading. Major scholars address Austen's six novels, the letters and other works, in terms accessible to students and the many general readers, as well as to academics. With seven new essays, the Companion now covers topics that have become central to recent Austen studies, for example, gender, sociability, economics, and the increasing number of screen adaptations of the novels--Provided by publisher.